Virtual source for a Mathieu–Gauss beam. (4th April 2017) - Dan, Li; Zhijun, Ren; Suyu, Deng
Abstract: We introduce a group of virtual sources for generating 2 n th-order even Mathieu–Gauss beams based on the beam superposition. Integral and differential representations are derived for a 2 n th-order even Mathieu–Gauss wave and the solution yields a corresponding 2 n th-order even paraxial Mathieu–Gauss beam in an appropriate limit. The first three orders of nonparaxial corrections for the on-axis field of the 2 n th-order even paraxial Mathieu–Gauss beam are obtained using the integral representation.